Messiness of forest governance: How technical approaches suppress politics in REDD+ and conservation projects - Myers, R.; Larson, A.M.; Ravikumar, A.; Kowler, L.F.; Yang, A.L.; Trench, T. (Elsevier, 2018)
Reduction of Emissions from Deforestation and Forest Degradation (REDD+) was originally conceived to address the global problem of climate change by reducing deforestation and forest degradation at national and subnational levels in developing countries. Since its inception, REDD+ proponents have increasingly had to adapt global ideas to local demands, as the rollout process was met with on-the-ground realities, including suspicion and protest. As is typical in aid or ‘development’ projects conceived in the global North, most of the solutions advanced to improve REDD+ tend to focus on addressing issues of justice (or ‘fairness’) in distributive terms, rather than addressing more inherently political objections to REDD+ such as those based on rights or social justice. Using data collected from over 700 interviews in five countries with both REDD+ and non-REDD+ cases, we argue that the failure to incorporate political notions of justice into conservation projects such as REDD+ results in ‘messiness’ within governance systems, which is a symptom of injustice and illegitimacy. We find that, first, conservation, payment for ecosystem services, and REDD+ project proponents viewed problems through a technical rather than political lens, leading to solutions that focused on procedures, such as ‘benefit distribution.’ Second, focusing on the technical aspects of interventions came at the expense of political solutions such as the representation of local people’s concerns and recognition of their rights. Third, the lack of attention to representation and recognition justices resulted in illegitimacy. This led to messiness in the governance systems, which was often addressed in technical terms, thereby perpetuating the problem. If messiness is not appreciated and addressed from appropriate notions of justice, projects such as REDD+ are destined to fail.